Analisis Pendekatan Saintifik pada Buku Sejarah Kebudayaan Islam Kurikulum 2013 Siswa MI Kelas 5 - Falia Rizma Safitri; Munawir Munawir (Departement of Mathematics Education, 2023)
The purpose of this study was to find out whether all the chapters in the 2013 curriculum subject Islamic Cultural History for 5th graders of Madrasah Ibtidaiyah are in accordance with the scientific approach or there are still learning steps that are not in accordance with the scientific approach. In this research method, the library research method was used which can be accessed qualitatively, the main source of which in this study was the textbooks for 5th grade students of Madrasah Ibtidaiyah students from the Islamic Cultural History subject for 5th graders of Madrasah Ibtidaiyah published by the Ministry of Religion in 2020 and sources of information supporting this study, namely articles, websites and other sources. The results of this study indicate that in the 2013 Curriculum the Islamic Cultural History subject book for grade 5 Madrasah Ibtidaiyah students incorporates a scientific approach. The existence of aspects of the scientific approach in the book can make the learning process active and innovative because this scientific approach is an approach used by educators to activate students in the learning process. This is in line with the 2013 curriculum which requires educators to apply a scientific approach in their learning, especially in thematic subjects, students must also conduct student-centered learning.